Impact study on “Moomin app in language learning in Larut, Matang and Selama education district” project - Abdul Manaf, Nor Faridah; Wok, Saodah; Wan Yusoff, Wan Mazwati; Md Zamin, Ainul Azmin; Abdul Rahman, Rozailin; Abdul Kadir, Hasnah (2021)
This study aims to measure the impact on the usage of Moomin Apps programme on students, teachers, parents and “Pejabat Pendidikan Daerah” (PPD) officers in Larut Matang dan Selama disctrict in Perak Darul Ridzwan. The number of respondents involved in the study consisted of 140 students, 30 teachers, 231 parents, and 8 PPD officers. The collected data were tested by using Statistical Package for the Social Sciences (SPSS). Overall, there are 13 objectives for this study. At the end of the study, different conclusions were derived based on each group’s respondents. From the students’ perspectives, they enjoyed the English lessons provided in the Moomin language app because the activities were always fun and exciting. From the teachers’ point of view, a majority of them regarded the Moomin language app as part of the “play” aspect which is important in their language pedagogy although face-to-face interaction is equally vital for class control and monitoring. Based on the parents’ feedback, they agreed that their children have to acquire the English language skills through learning and they need to monitor their performances. Finally, the PPD officers stated that the teachers lacked creativity, materials and some were not proficient in teaching English. They agreed that the face-to-face teaching method provided a better interaction between teachers and students. Even though this study faced with challenges especially during the data collection stage during the Covic-19 pandemic, the researchers managed to overcome the crucial part and proposed suggestions and recommendations for future usage.